FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN RAWAT INAP TERHADAP PELAKSANAAN KONSELING GIZI DI RUMAH SAKIT HOLISTIC PURWAKARTA - Astuti, Ipah Sri; Yani, Ahmad; Lisnawati, Naintina (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: So far nutrient service in Purwakarta Holistic Hospital never did evaluation about nutrient counseling service seen from medical patient satisfaction aspect. This evaluation process is very important because it is connected with aspects that to be the main priority in nutrient counseling service including counselor attitude, matter, media, method, time, and place of the counseling. Objective : To find out the factors which connected with hospitalization patients satisfaction toward nutrient counseling implementation in Purwakarta Holistic Purwakarta. Method : This research used obsevational with approach that used cross sectional. Number of research samples are about 32 people. Data which obtained are about nutrient counseling element, among counselor attitude, matter, media, method, time, and the place of the counseling. Data are obtained by questionnaires. Data analysis is Fisher Exact Test. Result : This research obtained that respondent assessment toward counselor attitude is 68,8% satisfied, counseling matter is 87,5% satisfied, media is 50% satisfied, counseling method is 46,9% satisfied, time of counceling is 96,9% satisfied,and place of counseling is 100% satisfied. Factors that related patient satisfaction toward nutrient counseling is counselor attitude (p=0,062), counseling matter (p=0,031), counseling media (p=0,469), counseling method (p =0,406),time of counseling (p=0,031), place of counseling (p=1,000). Conclusion: Factors that related patient satisfaction toward nutrient counseling are materials of counseling and time of counseling.